Association Of Selected Anthropometric And Body Composition Measures With Diet And Life Style Related Factors Among Punjabi Adult Males Of India (Applied Biological Research, 2016)
Occupational level greatly influences the physical activity which, in turn,  significantly affects body composition and overall health. Ninety adult  male participants in age group of 40-50 years from three occupational  categories i.e. field workers, laboratory workers and office workers were  selected from PAU, Ludhiana (India). The study revealed that higher  income and education were positively and significantly (p≤0.01)  correlated with body weight (r = 0.53; 0.48), BMI (r = 0.4; 70.44), waist  circumference (r = 0.65; 0.58) and fat mass (r = 0.37; 0.34), respectively.  Of the various activities carried out by participants, cycling and  agricultural activities showed a significant but negative relation with  body weight (r = -0.41, -0.86), BMI (r = -0.25, -0.38), waist circumference  (r = -0.62; -0.37) and fat mass (r = -0.39; -0.27) while positively  significant relationship was found with fat free mass (r = 0.31, 0.20).  Body fat accumulation was positively and significantly correlated with  body weight, BMI, waist circumference and fat mass, however, it was  proteins which had significant enhancing effect on fat free mass (r =  0.29). Therefore, it may be concluded that physical activity is a leading  factor that influences the anthropometry and body composition.
Keywords: Anthropometry body composition; field workers; laboratory workers; office workers